Teaching and Learning Psychotherapy: Lore Galore—Data Deficient - Hess, Allen K. (Contemporary psychology, 1995)
This is a review of the book, "Clinical Perspectives on Psychotherapy Supervision" (see record 1994-98377-000). The editors of "Clinical Perspectives on Psychotherapy Supervision" intend this volume to explore details of psychotherapy supervision as one way of balancing the growing biological orientation of psychiatry. They want psychiatrists to remember that the essence of helping people can never be divorced from listening and talking with people. The volume is heavily represented by teaching hospital (The University of Toronto and Mt. Sinai Hospital)-based senior clinicians who liberally pepper their chapters with case vignettes. With two exceptions, the authors are psychodynamic or unabashedly psychoanalytic. As such, the volume provides an excellent basis for the theory and practice of supervision. Edited books often have chapters written at disparate levels, focus, and content, leaving a reader befuddled. This book is evenly edited and largely forms an integrated whole. The lack of adequate indexes plagues many edited works. Regrettably, this book has a scant subject index and no author index. "Clinical Perspectives on Psychotherapy Supervision" summarizes material quite well in the context of discovery. (PsycINFO Database Record (c) 2016 APA, all rights reserved)